Relation between magnetization and Faraday angles produced by ultrafast spin-flip processes within the three-level Λ-type system - Hinschberger, Y.; Lavoine, J. P. (Journal of applied physics, 2015)
Ultrafast magneto-optical (MO) experiments constitute a powerful tool to explore the magnetization dynamics of diverse materials. Over the last decade, there have been many theoretical and experimental developments on this subject. However, the relation between the magnetization dynamics and the transient MO response still remains unclear. In this work, we calculate the magnetization of a material, as well as the magneto-optical rotation and ellipticity angles measured in a single-beam experiment. Then, we compare the magnetization to the MO response. The magnetic material is modeled by a three-level Λ-type system, which represents a simple model to describe MO effects induced by an ultrafast laser pulse. Our calculations use the density matrix formalism, while the dynamics of the system is obtained by solving the Lindblad equation taking into account population relaxation and dephasing processes. Furthermore, we consider the Faraday rotation of the optical waves that simultaneously causes spin-flip. We show that the Faraday angles remain proportional to the magnetization only if the system has reached the equilibrium-state, and that this proportionality is directly related to the population and coherence decay rates. For the non-equilibrium situation, the previous proportionality relation is no longer valid. We show that our model is able to interpret some recent experimental results obtained in a single-pulse experiment. We further show that, after a critical pulse duration, the decrease of the ellipticity as a function of the absorbed energy is a characteristic of the system.